2006
DOI: 10.1111/j.1365-2605.2006.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on the incidence of aneuploidy rates in spermatozoa of oligoasthenozoospermic patients and its relationship with ICSI outcome

Abstract: The development of intracytoplasmic sperm injection (ICSI) for treatment of infertility as a result of severe male factor has improved the chances of achieving pregnancy in many infertile couples. However, concerns have been raised regarding the safety of this technique, because natural sperm selection is bypassed. In the present study, 25 oligoasthenozoospermic patients who were divided into two groups according to age: group A, 20-34 (n = 10) and group B, 35-50 (n = 15), were included. Pooling the data of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
(66 reference statements)
1
7
1
Order By: Relevance
“…Some authors described an eVect of the donor's age on the frequency of sperm carrying numerical (Asada et al 2000;Bosch et al 2003) or structural chromosome abnormalities (Bosch et al 2003;Sloter et al 2007). By contrast, other authors did not Wnd this relationship (Kurahashi and Emanuel 2001;Plastira et al 2007). Contradictory results could be due to diVerences in the nature of the anomalies: age-dependent and age-independent anomalies could exist, explaining the diVerent results observed to-date.…”
Section: Susceptibility In Generating Deletions and Duplicationscontrasting
confidence: 47%
“…Some authors described an eVect of the donor's age on the frequency of sperm carrying numerical (Asada et al 2000;Bosch et al 2003) or structural chromosome abnormalities (Bosch et al 2003;Sloter et al 2007). By contrast, other authors did not Wnd this relationship (Kurahashi and Emanuel 2001;Plastira et al 2007). Contradictory results could be due to diVerences in the nature of the anomalies: age-dependent and age-independent anomalies could exist, explaining the diVerent results observed to-date.…”
Section: Susceptibility In Generating Deletions and Duplicationscontrasting
confidence: 47%
“…Although it is known that advanced maternal age is a risk factor for giving birth to children with aneuploidies, there are mixed results for the risk associated with advanced paternal age (62)(63)(64)(65).…”
Section: Fertility and Sterility âmentioning
confidence: 95%
“…Although some studies found no correlation (66,67), other investigators report an age effect, but exclusively on the rate of sex chromosome disomy (65,68). Furthermore, it should be mentioned that Plastira et al (65) found a higher rate of sex chromosome aneuploidy in younger men.…”
Section: Fertility and Sterility âmentioning
confidence: 96%
“…Also, the relationship between poor-quality semen and the development of embryos as well as clinical outcomes in patients undergoing ICSI is still uncertain (10)(11)(12). It can be reasoned that because spermatozoa were of limited number and good-quality sperm were chosen for ICSI, similar results might have been found after ICSI with different semen qualities (6,(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 93%